Highly-Skilled Migration: Between Settlement and Mobility IMISCOE Short Reader - Weinar, Agnieszka (IMISCOE Research Series, 2020)
This open access short reader discusses the emerging patterns of sedentary migration versus mobility of the highly-skilled thereby providing a comprehensive overview of the recent literature on highly-skilled migration. Highly-skilled migrations are arguably the only non-controversial migrant category in political and public discourse. The common perception is that highly-skilled migrants are high-earners with top educational skills and that they are easy to integrate. These perceptions make them a "wanted" migrant. There seems to be however a big divide between the popular perceptions of this migration and its realities uncovered in social research. This publication closes this divide by delving deeper in the variety of experiences, discourses and realities of highly skilled migrants, thereby uncovering the inherent divides between the highly skilled migrants from the North and the South. The reader shows that these divides are constructed realities, shaped by the state policies and underpinned by social imaginary. Written in an accessible language this reader is a perfect read for academics, students and policy makers and all those unfamiliar with the topic.